Synthesis and Antimicrobial Activity of Silver N-Methyl Chitosan - Kurniasih, Mardiyah; Purwati, Purwati; Dewi, Ratna Stia; Budiarni, Kasandra (Molekul, 2022)
This study synthesized silver N-methyl chitosan (Ag-NMC) and tested it for its antimicrobial and antifungal activity. Ag-NMC was characterized by FTIR, XRD, measured for its molecular weight (MW), solubility, and toxicity. The antimicrobial activity was tested by the agar diffusion method, determining the MIC (Minimum Inhibitory Concentration), MBC (Minimum Bactericidal Concentration) against Staphylococcus aureus and Escherichia coli bacteria, and determining the Minimum Fungicidal Concentration (MFC) against the fungus Candida albicans. The results showed that Ag-NMC had MW, solubility , and LC50 of 555.65 g/mol, 50 mg/mL, 945,492 mg/L, respectively. The diameter of the inhibition zone from the resulting https://www.surreyhillschallenge.com/ diffusion test showed that Ag-NMC had better antimicrobial activity than N-methyl chitosan (NMC) and chitosan. The MIC, MBC, and MFC values of Ag-NMC were always lower than that of NMC and chitosan.